Effect of growing conditions and sowing time on growth, yield and quality of fenugreek (Trigonella foenum-graecum) - PARMAR, D L; VERMA, PIYUSH; LEUA, H N; THAKAR, C J (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during September 2019 to January 2020 at College of Horticulture, Sardarkrushinagar Dantiwada Agricultural University, Jagudan, Gujarat to study the effect of various growing conditions and sowing time on growth, yield and quality of fenugreek (Trigonella foenum-graecum L.). In this investigation comprising of two factors, first one was different growing conditions which have 4 sub factors, viz. Open field, 50% green shadenet, 50% white shadenet and Naturally ventilated polyhouse and second one was different sowing time which also have 4 sub factors, viz. 3rd week of September, 1st week of October, 3rd week of October and 1st week of November which were tested in the SPD with 3 replications. Treatments were evaluated on the basis of growth, yield and quality characteristics of fenugreek. The 50% white shadenet and 3rd week of Oct reported minimum days for germination and harvesting, maximum plant height in all four cutting, yield attributes, viz. number of cutting, yield per cuttings, yield per ha in all cuttings, total yield per plot, total yield per ha and also the quality parameters, viz. chlorophyll a, b and total chlorophyll content and carotenoid content.